Increased residual lithium compounds guided design for green recycling of spent lithium-ion cathodes. Issue 3 (24th February 2021) - Fan, Min; Chang, Xin; Guo, Yu-Jie; Chen, Wan-Ping; Yin, Ya-Xia; Yang, Xinan; Meng, Qinghai; Wan, Li-Jun; Guo, Yu-Guo
Abstract : Based on the increased residual lithium compounds of the degraded cathode, a green water-based strategy is designed for achieving closed-loop recycling of spent lithium-ion batteries. Abstract : Recycling of spent lithium-ion batteries has recently become a critical issue based on environmental concerns and a desire to reutilize resources. Among the existing recycling strategies, direct regeneration is largely encouraged from an economic and environmental perspective. However, current procedures used to separate the active cathode materials from the aluminum foil have some limitations for direct regeneration because they either destroy the structure of the cathode or use too many toxic and expensive reagents. Hence, we conducted comprehensive research on the microstructural evolution of the LiNi1− x − y Co x Mn y O2 degraded electrode and then proposed a targeted method to recycle the spent cathode materials based on the increased residual lithium compounds. This separation process involves no other reagents but water, and toxic organic solvents, complicated processes, and waste treatments are unnecessary compared with the existing pretreatment strategies. Moreover, the separated cathodes are suitable for direct regeneration. Satisfactory capacity recovery of the cathode was achieved via simple sintering. Such a recycling process enables a sustainable closed-loop for the spent cathodes and provides new inspiration for the design of LIB recycling.